2016
DOI: 10.1371/journal.pone.0157645
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations of Segmented Macular Inner Layers in Aquaporin4-Antibody-Positive Optic Neuritis Patients in a Chinese Population

Abstract: ObjectivesThis study aimed to analyse the structural injury of the peripapillary retinal nerve fibre layer (pRNFL) and segmented macular layers in optic neuritis (ON) in aquaporin4-antibody (AQP4-Ab) seropositivity(AQP4-Ab-positiveON) patients and in AQP4-Ab seronegativity (AQP4-Ab-negative ON) patients in order to evaluate their correlations with the best-corrected visual acuity (BCVA) and the value of the early diagnosis of neuromyelitis optica (NMO).DesignThis is a retrospective, cross-sectional and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
5
12
1
Order By: Relevance
“…The latter ON is likely to progress to MS or isolated ON after frequent recurrences of ON in clinical practice. Previously, studies about structural injuries by OCT in NMO-ON and AQP4-Ab+/ON (NMOSD) versus AQP4-Ab−/ON were scarce 4. However, for NMO-ON versus MS-ON, there have been many studies8–13 in recent years, as well as the present study, that showed that NMO-ON caused more damage in the pRNFL and inner macular segmented layers.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The latter ON is likely to progress to MS or isolated ON after frequent recurrences of ON in clinical practice. Previously, studies about structural injuries by OCT in NMO-ON and AQP4-Ab+/ON (NMOSD) versus AQP4-Ab−/ON were scarce 4. However, for NMO-ON versus MS-ON, there have been many studies8–13 in recent years, as well as the present study, that showed that NMO-ON caused more damage in the pRNFL and inner macular segmented layers.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, AQP4-Ab+/ON is considered an early or limited type of NMO and has been named an NMO spectrum disorder (NMOSD). Our previous study also demonstrated that AQP4-Ab+/patients with ON had injury patterns distinct from those of AQP4-Ab seronegative ON (AQP4-Ab−/ON) patients in the peripapillary retinal nerve fibre layer (pRNFL) and inner nuclear layer (INL) and measurements of AQP4 -Ab levels were more important in patients with ON who will develop NMO compared with other autoantibodies 4 5. However, the pathogenesis of definite NMO involves more than AQP4-Ab+/ON.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The superior and inferior quadrants of pRNFL were preferentially damaged in AQP4-ON eyes compared with the MOG-ON eyes, which is consistent with previous studies. This may be because AQP4 is strongly expressed in the superior and inferior quadrants of the pRNFL with plenty of vessels and facing vitreous bodies, which can cause parallel and more severe injury and induce more pRNFL thinning in AQP4-ON eyes 5. Our study also found damage preferentially occurred in the superior, temporal inferior and temporal superior quadrants of the mGCIPL in AQP4-ON eyes compared with MOG-ON eyes.…”
Section: Discussionsupporting
confidence: 48%
“…In the Chinese population, NMO is the more common central nervous system inflammatory demyelinating disorder 5. The presence of aquaporin-4 (AQP4) antibody is an important biomarker for neuromyelitis optica spectrum disorders (NMOSDs) 6 7.…”
Section: Introductionmentioning
confidence: 99%